2020
DOI: 10.1111/inm.12820
|View full text |Cite
|
Sign up to set email alerts
|

Stigma in relation to families living with parental mental illness: An integrative review

Abstract: Stigma is a pervasive social mechanism with negative ramifications for people who experience mental illness. Less is known about the stigma experiences of families where a parent has a mental illness. This review aims to identify and synthesize evidence on the concept of stigma and stigma-related experiences and outcomes reported by parents and children living with parental mental illness. An integrative review method was employed, with PRISMA (Preferred Reporting Items of Systematic Review and Meta-Analyses) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 83 publications
6
49
0
Order By: Relevance
“…Possibly because of public stigma, mothers in this study reported a lack of confidence in their parenting, and guilt about their children, consistent with other studies in the West and Japan [ 6 , 7 , 11 , 13 ]. Reupert et al [ 38 ] argued that the (in) ability of mothers to fulfil the socially standardized gender role and idealized parenting role underpins the stigmatization associated with being a mother with mental illness. The pervasive nature of stigma, described by the mothers in this study, poses a threat to their recovery and help-seeking [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Possibly because of public stigma, mothers in this study reported a lack of confidence in their parenting, and guilt about their children, consistent with other studies in the West and Japan [ 6 , 7 , 11 , 13 ]. Reupert et al [ 38 ] argued that the (in) ability of mothers to fulfil the socially standardized gender role and idealized parenting role underpins the stigmatization associated with being a mother with mental illness. The pervasive nature of stigma, described by the mothers in this study, poses a threat to their recovery and help-seeking [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reupert et al [ 38 ] argued that the (in) ability of mothers to fulfil the socially standardized gender role and idealized parenting role underpins the stigmatization associated with being a mother with mental illness. The pervasive nature of stigma, described by the mothers in this study, poses a threat to their recovery and help-seeking [ 38 , 39 ]. It also may stop them from talking to children about their illness, as others have found [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In families with a parent with a psychotic disorder, who are additionally disproportionately affected by parental unemployment, isolation and poverty ( 11 ) these impacts may be even greater. Psychosis has been found to interfere with the establishment and maintenance of important family routines ( 12 ) and stigmatization may serve to prevent help-seeking in families that are struggling ( 13 , 14 ). Ultimately, children of parents with schizophrenia and other psychotic disorders are more likely to be removed from their parents' care ( 15 , 16 ) with long term consequences for both parent and children's well-being and at significant economic cost for wider society.…”
Section: Introductionmentioning
confidence: 99%
“…
We read with great interest the article entitled 'Stigma in relation to families living with parental mental illness: An integrative review' by Reupert et al (2021). The authors used the integrative review method proposed by Whittemore and Knafl ( 2005), which emphasizes the importance of conducting a thorough quality appraisal of the included articles.
…”
mentioning
confidence: 99%